2023
DOI: 10.1111/bph.16087
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized soluble guanylyl cyclase causes erectile dysfunction in alcoholic mice

Abstract: Background and purposeAlcohol abuse has been associated with erectile dysfunction (ED), but the implicated molecular mechanisms are unresolved. This study analyses the role of alterations in soluble guanylyl cyclase (sGC) in ED.Experimental approachED was analysed in adult male C57BL/6J mice subjected to the Chronic Intermittent Ethanol (CIE) paradigm. Erectile function was assessed in anaesthetised mice in vivo by evaluating intracavernosal pressure (ICP) and in vitro in isolated mice corpora cavernosa (CC) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A significant relationship between alcohol consumption and ED was observed in this study, which is consistent with previous studies. 22 We used drinks per week as a phenotype of alcohol intake in the research, which is defined as the average number of drinks a participant reported drinking each week, aggregated across all types of alcohol. If a study recorded binned response ranges, we used the midpoint of the range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant relationship between alcohol consumption and ED was observed in this study, which is consistent with previous studies. 22 We used drinks per week as a phenotype of alcohol intake in the research, which is defined as the average number of drinks a participant reported drinking each week, aggregated across all types of alcohol. If a study recorded binned response ranges, we used the midpoint of the range.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if an individual reported 1 to 5 drinks per week, we assume that they drank 2.5 drinks per week on average. 15 Animal experiments have shown that 22 chronic exposure to alcohol reduces the relaxation response of the corpus cavernosum in vitro through neurogenic and endothelial pathways while attenuating the physiological process of increased pressure in the corpus cavernosum caused by bioelectrical conduction in vivo. Besides, frequent use of alcohol reduces libido and makes it difficult for men to achieve erections or orgasms.…”
Section: Discussionmentioning
confidence: 99%